The Visuospatial Episodic Memory in Persian-speaking Patients with Multiple Sclerosis - Sara Yazdani; Shahla Sharifi; Mohsen Foroughipour; Atiyeh Kamyabgol (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Memory dysfunction is one the most common challenges of patients with Multiple Sclerosis (MS). Memory has a major role in daily life and influences social communication of individuals. The aim of this research was to investigate the function of nonverbal episodic memory in Persian speaker patients with MS. Materials and methods: In this cross-sectional study, 46 patients (13 males and 33 females) with definite relapsing-remitting multiple sclerosis and 46 age, gender, and educationally-matched healthy controls were selected using convenient sampling based on inclusion criteria. The patients were divided into two groups (n=23 per group) according to the Expanded Disability Status Scale (EDSS) scores; 0-4 and 4-6. The Montreal Cognitive Assessment (MoCA) test was used to screen cognitive function and the Benson Figure test was used to evaluate the non-verbal episodic memory function. Results: Compared to healthy controls, both MS groups were found to be significantly impaired in accuracy and placement of structures of visuospatial abilities (copy trial), visual memory (immediate recall), and maintaining and retrieving visuospatial sources (delayed recall) (P< 0.05). Conclusion: Acquired brain injury in MS is associated with dysfunction of nonverbal episodic memory. In other words, MS would adversely influences patient’s performance in all stages of the visuospatial test (copy, immediate, and delayed recall). Moreover, EDSS could be regarded as a predictor for individual differences in MS patients in all stages of nonverbal episodic memory.